Impact of China on Malaysian economy: Empirical evidence of sign-restricted structural vector autoregresion (SVAR) model - Zaidi, Mohd Azlan Shah; Karim, Zulkefly Abdul; Zurina Kefeli@ Zulkefli (Penerbit Universiti Sains Malaysia, 2024)
Indexed by WOS/Scopus